2006
DOI: 10.1159/000094164
|View full text |Cite
|
Sign up to set email alerts
|

Large Animal Models of Traumatic Injury to the Immature Brain

Abstract: Large animal models have been used much less frequently than rodent models to study traumatic brain injury. However, large animal models offer distinct advantages in replicating specific mechanisms, morphology and maturational stages relevant to age-dependent injury responses. This paper reviews how each of these features is relevant in matching a model to a particular scientific question and discusses various scaling strategies, advantages and disadvantages of large animal models for studying traumatic brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 113 publications
1
68
0
Order By: Relevance
“…[4][5][6] This also makes piglets particularly well suited to studies of pediatric populations, and the immature piglet model of TBI has been shown to have many similar findings observed in infant TBI. 17,22 Furthermore, this infant piglet model exhibits an injury pattern and severity that is dependent upon rotational plane, similar to experimental and finite element findings in primates and humans. 12,[14][15][16] Unfortunately, there is a paucity of validated behavioral tests for the immature piglet model, and those used on rodents do not translate well to pigs because of their different motor abilities, handling needs, and responses to stimuli (e.g., the well-known aversion of mice to light and open spaces is not observed in pigs).…”
Section: Discussionsupporting
confidence: 72%
“…[4][5][6] This also makes piglets particularly well suited to studies of pediatric populations, and the immature piglet model of TBI has been shown to have many similar findings observed in infant TBI. 17,22 Furthermore, this infant piglet model exhibits an injury pattern and severity that is dependent upon rotational plane, similar to experimental and finite element findings in primates and humans. 12,[14][15][16] Unfortunately, there is a paucity of validated behavioral tests for the immature piglet model, and those used on rodents do not translate well to pigs because of their different motor abilities, handling needs, and responses to stimuli (e.g., the well-known aversion of mice to light and open spaces is not observed in pigs).…”
Section: Discussionsupporting
confidence: 72%
“…No widespread hypoxicischemic brain damage was observed in any animal, perhaps because of the lower sensitivity of sheep to hypoxia-ischemia insults compared with humans and pigs. 29 In summary, within 6 h of shaking, this large animal model with uncontrolled repeated head movements did not produce widespread hypoxic-ischemic brain injury, subarachnoid or subdural hemorrhage, and retinal hemorrhage, which are characteristics often noted in AHT patterns attributed to shaking.…”
Section: Introductionmentioning
confidence: 59%
“…We evaluated female five-day-old and four-week-old piglets, of which the brain development corresponds to the human infant and the human toddler, respectively. 24,25 Animals met the inclusion criteria if they: 1) experienced no injury or a single rapid non-impact rotational injury (RNR) in the sagittal plane; 2) were not given any treatments; 3) were sacrificed for neuropathology; and 4) had post-TBI survival times of 3 h to six days. This criteria included 55 five-day-old piglets and 40 four-week-old piglets.…”
Section: Methodsmentioning
confidence: 99%
“…9,17,23 The gyrencephalic piglet brain is similar to the human brain in growth patterns, gray and white matter distribution, and cerebrovascular anatomy and physiology, making it a good translational model. [24][25][26][27] We sought to determine when TAI and ICH reach their peak post-injury, how long they remain elevated, and if their progression is age dependent; provide insight into the optimal window for clinical intervention and the period of increased vulnerability to a second injury; and glean further information about age-specific vulnerabilities that have been observed.…”
mentioning
confidence: 99%